Relevansi Sistem Kewarisan Matrilineal Minangkabau dalam Masyarakat Kontemporer - Tengku Rizki Rahman; Muhammad Saputra (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The matrilineal inheritance system of the Minangkabau represents one of the most distinctive customary inheritance models in Indonesia. In this system, ancestral property (harta pusaka) is inherited through the maternal line, placing women at the center of the family's social and economic structure. However, contemporary societal dynamics characterized by social and economic change, as well as the influence of state law and Islamic legal norms have posed significant challenges to the sustainability of this system. This study aims to examine the relevance of the Minangkabau matrilineal inheritance system in today’s context, with particular attention to sociological aspects, customary law, and Islamic law. Employing a qualitative-descriptive approach, this research is based on literature studies and interviews with traditional leaders and legal scholars. The findings indicate that the customary inheritance system continues to play a vital role in maintaining the identity and social structure of Minangkabau society. Nonetheless, normative adjustments are necessary to ensure alignment with principles of gender justice and positive law. Therefore, a thoughtful integration of adat, religion, and state law is essential to ensure the continuity of the Minangkabau inheritance system in the modern era.